2010
DOI: 10.1007/s11103-010-9722-4
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and gene expression analyses of a ploidy series of maize inbred Oh43

Abstract: Polyploidization has repeatedly occurred during plant evolution. Although autopolyploidy is the best model to characterize the polyploidization effects in a highly controlled manner, there are limited studies on autopolyploids compared to allopolyploids. To improve our understanding of autopolyploidy effects in maize, we developed an inbred Oh43 ploidy series consisting of the diploid (2X), tetraploid (4X) and hexaploid (6X) lines and compared their phenotypes and gene expression in the mature adult leaf tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…In a corn ploidy series, a pioneering paper by Guo et al (1996) reported that expression of most genes analyzed increased with polyploidization, whereas some others showed an opposite trends. Genes that were positively or negatively modulated by autopolyploidization have been reported also by Yao et al (2011) comparing 2x, 4x and 6x corn lines. Yu et al (2010) confirmed a genotype-specific gene expression change in analysing three selected genes in A. thaliana ecotypes.…”
Section: Discussionmentioning
confidence: 75%
“…In a corn ploidy series, a pioneering paper by Guo et al (1996) reported that expression of most genes analyzed increased with polyploidization, whereas some others showed an opposite trends. Genes that were positively or negatively modulated by autopolyploidization have been reported also by Yao et al (2011) comparing 2x, 4x and 6x corn lines. Yu et al (2010) confirmed a genotype-specific gene expression change in analysing three selected genes in A. thaliana ecotypes.…”
Section: Discussionmentioning
confidence: 75%
“…Though translatomic approaches have been used to study regulation of gene expression in plants (Kawaguchi et al, 2004;Jiao and Meyerowitz, 2010;Mustroph and Bailey-Serres, 2010;Juntawong and Bailey-Serres, 2012), few studies have examined gene expression downstream of transcription in recent polyploids (Albertin et al, 2006(Albertin et al, , 2007Hu et al, 2011Hu et al, , 2013Yao et al, 2011), and none have specifically examined translational regulation. Here, we have shown that the transcriptome and translatome of a recently formed allotetraploid (G. dolichocarpa T2) related to soybean were highly correlated overall but that ;10% of genes in each duplicated subgenome (homoeologs) exhibited significant translational regulation, and 10% exhibited translational regulation of combined expression.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of studies in polyploids have examined expression at the protein level (Albertin et al, 2006(Albertin et al, , 2007Hu et al, 2011Hu et al, , 2013Yao et al, 2011), but due to both technical and biological constraints, these studies have provided data on homoeologspecific expression for only a small number of genes (Hu et al, 2011(Hu et al, , 2013Koh et al, 2012). Additionally, protein abundance is the net result of transcription, translation, and other regulatory steps (e.g., mRNA degradation) and does not therefore provide direct information about the contributions of these steps individually.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent studies using 2-DE indicated numerous and non-stochastic modifications of proteins in resynthesized Brassica napus (Albertin et al, 2006(Albertin et al, , 2009 and wheat hybrids (Song et al, 2007). Using protein 2-DE coupled with mass spectrometry (MS) assays, a recent study showed a positive correlation of differentially expressed proteins with ploidy levels in a maize ploidy series (diploid, tetraploid and hexaploid) (Yao et al, 2011). However, the highest correlations were found in diploid-hexaploid and tetraploid-hexaploid comparisons rather than in the diploid-tetraploid comparison.…”
Section: Introductionmentioning
confidence: 99%